2022
DOI: 10.1002/adhm.202200965
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Vascular Stents with Microfluidic Electrospun Multilayer Coatings for Preventing In‐Stent Restenosis

Abstract: In‐stent restenosis (ISR) is seriously affecting the long‐term prognosis of vascular interventional therapy and leading to enormous medical burdens. Great efforts have been devoted to developing functional vascular stents with desired features and properties for effective ISR prevention. Here, a multifunctional bionic vascular stent with designed coatings prepared using microfluidic electrospinning technology is presented. Such stents are composed of biocompatible, drug‐loaded methylacrylated gelatin‐polyethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…[43] This process could be improved by releasing proangiogenic factors, such as VEGF, basic fibroblast growth factor (bFGF), PDGF and their plasmids, in an individual or coordinated manner. [44] On the other hand, the postoperative inflammatory response and potential for rejection could be mitigated to reduce vascular long-term stenosis by downregulating the expression of TGF-𝛽1. [45,46] Therefore, we propose the sequentially controlled release of VEGF and a TGF-𝛽1 inhibitor via a dual-release system as a promising strategy to regulate integration throughout the remodeling process.…”
Section: Discussionmentioning
confidence: 99%
“…[43] This process could be improved by releasing proangiogenic factors, such as VEGF, basic fibroblast growth factor (bFGF), PDGF and their plasmids, in an individual or coordinated manner. [44] On the other hand, the postoperative inflammatory response and potential for rejection could be mitigated to reduce vascular long-term stenosis by downregulating the expression of TGF-𝛽1. [45,46] Therefore, we propose the sequentially controlled release of VEGF and a TGF-𝛽1 inhibitor via a dual-release system as a promising strategy to regulate integration throughout the remodeling process.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, patients often face various vascular diseases such as myocardial infarction, endothelial disease, and peripheral vascular disease. In cases where their own blood vessels are insufficient for repair, extracorporeal implantation of vascular stents becomes necessary ( Cheng et al, 2022 ). Although allogeneic or xenogeneic vascular grafts can be used as substitutes, immune rejection reactions are a common concern, limiting their practicality.…”
Section: Zif-8 Based Tissue Engineering Scaffoldmentioning
confidence: 99%
“…Another study showed that a 5-layer chondroitin 6-sulfate (ChS)-HEP-modified MSS stent displayed the greatest hemocompatibility, prolonged blood clotting time, activated partial thrombin time (aPTT), and reduced platelet adhesion to reduce thrombosis [210]. In a study, methyl acrylate gelatin-polyethylene glycol diacrylate (GelMA-PEGDA) and polycaprolactone composite nanofibers composite loaded with rapamycin were sprayed step-by-step on MSS and reported to have improved anti-thrombosis and in-stent restenosis effects [211].…”
Section: Improvement Of Hemocompatibilitymentioning
confidence: 99%